A Case Report Conservative Treatment of Huge Bladder Neurofibroma - Jaharudin, Mohd Azrul Eimirul; Ahmed Fahmy, Omar Fahmy; Lee Kheng Siang, Christopher; Mohd Ghani, Khairul Asri; Shau Kong, Lai (The Interventionalist Journal, 2022)
Neurofibroma with involvement of the urinary bladder is a rare condition, that has been reported in less than 80 cases reported worldwide. We present a 22-year-old lady with a known history of childhood neurofibroma type 1. Incidental findings of a huge pelvic mass during laparoscopic surgery for initially thought of a gynae pathology. Further investigation after that with Computed Tomography (CT) scan displayed a bladder mass occupying the abdomen cavity with regards to neurofibroma of the bladder. A core Biopsy of the mass was done and confirmed the pathology. Clinically patient was asymptomatic with the mass. The patient refused surgical intervention. Follow-up for 2 years with serial imaging showed no significant progression of the disease. It is important to determine any Sarcomatoid/malignant changes to decide on further management of bladder neurofibroma.